2020
DOI: 10.1177/1758835920967241
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of tumor-infiltrating lymphocytes in high grade serous ovarian cancer: a systematic review and meta-analysis

Abstract: Background: Tumor-infiltrating lymphocytes (TILs) are involved in the antitumor immune response. The association between prognosis in patients with TILs and high-grade serous ovarian cancer (HGSOC) remains obscure, with some studies reporting conflicting results. Methods: We conducted an extensive literature search of electronic databases and retrieved prognostic data of each selected subtype of TILs, including CD3+, CD4+, CD8+, CD103+, and PD-1+ TILs. The fixed-effects model was applied to derive the pooled h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 47 publications
5
28
1
Order By: Relevance
“…This low number of T-cells is in keeping with findings of multiple investigators that PCa is an immunologically “cold” tumor with low numbers of tumor infiltrating lymphocytes (TILs) [19] . Although various definitions and quantification methods have been used for TILs, CD3 + total T-cells and subsets, especially CD8 + T-cells are shown in other cancers to correlate with survival [20] , [21] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This low number of T-cells is in keeping with findings of multiple investigators that PCa is an immunologically “cold” tumor with low numbers of tumor infiltrating lymphocytes (TILs) [19] . Although various definitions and quantification methods have been used for TILs, CD3 + total T-cells and subsets, especially CD8 + T-cells are shown in other cancers to correlate with survival [20] , [21] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, adipose tissues can secrete many types of cytokines and molecular factors to recruit macrophages to attenuate T cell function ( 52 , 53 ). Several research studies have investigated the correlation between TIL and prognosis of OC and identified several T cell predictive biomarkers, such as CD4, CD8, CD3, CD103, and PD-1 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies and the results in this study, effects of MAP3K8 on cancer-related inflammation in ccRCC may be double-edged. On one hand, ccRCC patients with highlevel expression of MAP3K8 negatively correlated with the presence of T cell CD4 + Th1, non-regulatory T cell CD4 + , and NK cell, suggesting a potential protumorigenic role of MAP3K8 because CD4 + TILs and NK cells were reported to associate with better OS in cancers (Hao et al, 2020). In addition, CD4 + Th1 secreting cytokines such as TNF may effectively inhibit angiogenesis as well as facilitate the activation and proliferation of CD8 + TILs, which could directly kill tumor cells (Ovarian Tumor Tissue Analysis [OTTA] Consortium, Goode et al, 2017;Hao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%